Disease mechanism and novel drug therapies for atrial fibrillation - Wiedmann, Felix Tobias; Schmidt, Constanze (Medizinische Genetik, 2025)
Atrial fibrillation (AF), the most common sustained cardiac arrhythmia, affects over 3 % of adults globally, increasing risks for stroke, heart failure, and cognitive decline. Early rhythm control shows promise in improving AF prognosis, and catheter ablation remains an effective, safe option, especially for paroxysmal AF. However, high recurrence rates with antiarrhythmic drugs and ablation persist, particularly in cases of persistent AF. Emerging research on molecular mechanisms has led to innovative therapeutic strategies targeting these pathways, offering hope for more effective AF management. This review explores recent insights into the complex pathophysiology of AF, with a particular focus on ion channel dysfunction, calcium mishandling, oxidative stress, and fibrosis. It further considers how these factors will inspire new therapeutic options.